Wearable neurotechnology systems for upper extremity rehabilitation in children with cerebral palsy: a scoping review - Burchfield, Sara Jo; Shierk, Angela; Truong, Cindy; Blankenship, Regan (Frontiers in Neurology, 2025)
BackgroundChildren with cerebral palsy often experience persistent upper extremity impairments that impact independence and participation in daily activities. Wearable neurotechnology devices offer a promising, non-invasive approach to enhance motor control, promote neuroplasticity, and extend neurorehabilitation beyond clinical settings. However, the development and application of such devices in pediatric populations remains poorly defined. This scoping review aimed to map the existing literature on wearable neurotechnology systems used for upper extremity rehabilitation in children with cerebral palsy and identify knowledge gaps to guide future research and clinical translation in pediatric neurorehabilitation.MethodsThis review followed the JBI Scoping Review Methodology and PRISMA-ScR guidelines. Four electronic database sources, MEDLINE, Scopus, CINAHL, and PsycINFO, were systematically searched to identify studies on wearable neurotechnology devices for upper extremity rehabilitation in children with cerebral palsy. Included studies consisted of journal articles published from January 2005 to June 2025, with full texts available in English and relevant gray literature sources. Data were extracted on neurotechnology characteristics, regulatory status, intervention protocols, and outcome measures.ResultsFrom the 2,892 articles screened, 21 met the eligibility criteria. Most devices were in early developmental stages, with only five receiving regulatory approval. Studies examined various systems, including electromyography-triggered stimulation, virtual reality, and robot-assisted devices with haptic or electrical stimulation, and wearable garments embedded with electrical or vibrotactile stimulators. Intervention protocols varied widely across studies in terms of treatment intensity, wear schedules, and co-interventions. Feasibility was generally positive across studies, with high adherence rates and minimal adverse events reported. Many studies reported improvements in motor outcomes, including enhanced grip strength, hand use, range of motion, grasp and release ability, and muscular recruitment.ConclusionsWearable neurotechnology shows potential to augment upper extremity rehabilitation in children with cerebral palsy, particularly through systems that support task-specific, feedback-driven practice. However, translation to clinical practice is limited by heterogeneity in device design, lack of standardized protocols, and limited high-quality evidence. Future research should prioritize standardization, clinician-centered implementation studies, and long-term outcomes to support integration into pediatric care.Systematic review registrationhttps://osf.io/5qxpe.